Relationship of added sugars intakes with physiologic parameters in adults: an analysis of national health and nutrition examination survey 2001-2012 - Carol E O'Neil; Theresa A Nicklas; Rabab Saab; Victor L Fulgoni (AIMS Press, 2020)
Introduction: Consumption of added sugars (AS) has been associated with increased risk for liver disease and risk factors for cardiovascular disease. The objective of this study was to further understand the relationship of AS intake with liver enzymes and risk factors for cardiovascular disease in adults (n = 29,687) participating in the National Health and Nutrition Examination Survey (NHANES) 2001-2012. Methods: Individual usual intake (IUI) of AS was estimated using the Markov Chain Monte Carlo ratio method using two days of 24-hour dietary recalls gathered using standardized protocols. Subjects were separated into six consumption groups: 0 to <5%, 5 to <10%, 10 to <15%, 15 to <20%, 20 to <25% and ≥25% of energy as added sugars. Linear and group trends were determined using regression analyses for liver enzymes, cardiovascular risk factors, weight parameters, glucose, metabolic syndrome, and C-reactive protein. Logistic regression calculated odds ratios for these biomarkers above established risk levels (p < 0.01). Results: There was an inverse group trend association with AS IUI for lower body mass index (beta = −0.12 kg/m 2 across AS intake groups); % overweight/obese or % obese also showed inverse group trend (−1.44, −0.77, % units across AS intake groups, respectively). Liver enzymes did not show a significant association with AS IUI. Mean plasma glucose levels (mg/dL) showed an inverse linear (beta = −0.13 mg/dL per AS intake); and group association with energy from AS IUI (beta = −0.71mg/d L across AS intake groups). There was no association of AS intake with the risk of elevated uric acid levels; however, the odds of reduced uric acid levels was 17% lower with increasing intake of energy from AS IUI in group trend analysis only (0.83; 0.72-0.95 [99th CI]). Conclusion: Although it is sensible to consume AS in moderation, results suggested that higher intakes of AS were not consistently associated with physiologic parameters. Since the data were cross-sectional, they cannot be used to assess cause and effect. Thus, additional studies are warranted to confirm these findings with more rigorous study designs.